2007
DOI: 10.1007/s00424-007-0362-8
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of ventricular contractility in mice: influence of load and sensitivity to changes in inotropic state

Abstract: We examined the relative usefulness of parameters to determine left ventricular contractility in mice invasively. The optimal parameter must be sensitive to changes in inotropy and insensitive to changes in loading. Furthermore, it should be able to confirm or reject the hypothesis of altered myocardial contractility after a limited number of experiments. Left ventricular function was assessed in closed-chest mice using a microtip pressure-conductance catheter at baseline and after increases in preload, afterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Finally, many invasive parameters have been proposed to accurately reflect myocardial contractile function. However, PRSW has recently been shown to be an optimal measure of contractility in mice as it is independent of preload and afterload (23). Although each of the parameters prospectively chosen to represent preload, afterload, and contractility have their limitations, they would seem the most appropriate independent approximations in this experimental setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, many invasive parameters have been proposed to accurately reflect myocardial contractile function. However, PRSW has recently been shown to be an optimal measure of contractility in mice as it is independent of preload and afterload (23). Although each of the parameters prospectively chosen to represent preload, afterload, and contractility have their limitations, they would seem the most appropriate independent approximations in this experimental setting.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the pressure-volume loop data sets was performed with PVAN 3.2 software (Millar Instruments). The maximal rate of developed LV pressure (dP/dtmax), maximal value of time-varying elastance, end-systolic elastance (Ees), arterial elastance (Ea), and preload recruitable stroke work (PRSW) were measured as previously described (23). The maximal rate of pressure decay (dP/dt min) and time constant of isovolumic relaxation were also obtained.…”
Section: This Investigation Conformed With the National Institutes Ofmentioning
confidence: 99%
“…Two studies have demonstrated enhanced ␤-adrenergic dP/dt max in eNOS Ϫ/Ϫ mice with Iso (10,19). However, dP/ dt max is known to be sensitive to afterload (44), suggesting that the innate hypertension in eNOS Ϫ/Ϫ mice may have influenced prior results (10,19). It is also possible that no differences were detected between eNOS Ϫ/Ϫ and WT mice as a result of the relatively low dose of Dob used.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how this arises because this effect is absent in isolated right atrium. Especially, the difference in preload recruitable stroke work is important because it is independent of the preload of the heart 21,22 and illustrates that the intrinsic inotropic status of the Trpm4 −/− muscle is enhanced compared with WT after β-adrenergic stimulation. In accordance with and sarcomere contraction strength (see for instance), 23 even a limited increase in the Ca 2+ transient will have a profound effect on contraction strength.…”
Section: +mentioning
confidence: 99%